(untitled) (The Review of Diabetic Studies, 2025)
Background: Insulin sensitivity plays a pivotal role in determining the effectiveness of insulin therapy in type 2 diabetes mellitus (T2DM). Understanding how insulin responsiveness interacts with therapeutic regimens is vital for optimizing glycemic outcomes. Methods: This systematic review and meta-analysis followed PRISMA 2020 guidelines and synthesized data from 11 eligible peer-reviewed studies (2005–2025). Databases including PubMed, Scopus, Embase, and Web of Science were searched using standardized Boolean terms. Eligible studies evaluated insulin sensitivity indices (HOMA2-%S, KITT, M-value) and glycemic parameters (HbA1c, fasting glucose) before and after insulin-based interventions. Results: Across studies, insulin therapy significantly improved insulin sensitivity by 15–40% (p < 0.001) and reduced HbA1c by an average of 1.4–2.6% in previously uncontrolled T2DM patients. Intensive insulin regimens, such as insulin glargine/lixisenatide and insulin degludec/aspart, produced superior improvements in both insulin sensitivity and β-cell function recovery compared to conventional or oral therapies alone. Studies demonstrated that early insulinization enhanced remission rates and restored β-cell responsiveness in newly diagnosed patients. However, acidosis, muscle mass loss, and overtreatment in older adults reduced therapeutic benefit and increased hypoglycemia risk. Conclusion: Insulin therapy substantially enhances insulin sensitivity and glycemic control, particularly when initiated early and tailored to patient characteristics. However, treatment optimization requires balancing efficacy with safety, emphasizing the need for individualized approaches integrating metabolic and physiological parameters.